(untitled) (Bangladesh Pharmaceutical Journal, 2022)
The objective of this study is to investigate the prescription pattern of proton pump inhibitors (PPIs) in association with patients’ age, gender and type of hospital visited (government or private), location of the hospital and doctors’ specialty in major divisions of Bangladesh. The secondary objective of this study was to analyze the current market size, share and growth of PPIs in the antiulcer drug market. A crosssectional survey of drug prescriptions was done at hospitals and clinics (private practices) between April 2021 to June 2021 of 7 divisions in Bangladesh. A total of 386 prescriptions, containing 2354 medicines, from 21 districts/areas of 7 divisions in Bangladesh were reviewed to determine the trend of prescribing PPIs. Market data of PPIs were collected from a secondary source (IQVIA). The data collected from the survey were tabulated, analyzed and graphically presented using Microsoft Office Excel 2016. Collected data were entered into the SPSS19.0 statistical software “R” and analyzed. Prescribed antiulcer drugs included Esomeprazole (70.2%), Rabeprazole (7.8%), Omeprazole (4.7%), Dexlansoprazole (4.4%), Pantoprazole (3.1%), and Lansoprazole (0.3%); and 9.3% of collected prescriptions had no anti-ulcerant. There was no association between gender and PPIs prescribed, nor across the type of hospital visited. Only the regression coefficient relating to the patient’s age is statistically significant (β=0.01, p<0.05) in overall drug consumption. Along with nonspecific explanations, there were twelve specific reasons for prescribing antiulcer drug generics where the majority of the cases were attributed to NSAID-induced acidity (36%). Bangladesh Pharmaceutical Journal 25(2): 209-217, 2022 (July)